The immunosuppression pathway of tumor‐associated macrophages is controlled by heme oxygenase‐1 in glioblastoma patients. Issue 12 (15th September 2022) - Magri, Sara; Musca, Beatrice; Pinton, Laura; Orecchini, Elena; Belladonna, Maria Laura; Orabona, Ciriana; Bonaudo, Camilla; Volpin, Francesco; Ciccarino, Pietro; Baro, Valentina; Della Puppa, Alessandro; Mandruzzato, Susanna
Abstract: The immunosuppressive tumor microenvironment (TME) in glioblastoma (GBM) is mainly driven by tumor‐associated macrophages (TAMs). We explored whether their sustained iron metabolism and immunosuppressive activity were correlated, and whether blocking the central enzyme of the heme catabolism pathway, heme oxygenase‐1 (HO‐1), could reverse their tolerogenic activity. To this end, we investigated iron metabolism in bone marrow‐derived macrophages (BMDMs) isolated from GBM specimens and in in vitro‐derived macrophages (Mφ) from healthy donor (HD) blood monocytes. We found that HO‐1 inhibition abrogated the immunosuppressive activity of both BMDMs and Mφ, and that immunosuppression requires both cell‐to‐cell contact and soluble factors, as HO‐1 inhibition abolished IL‐10 release, and significantly reduced STAT3 activation as well as PD‐L1 expression. Interestingly, not only did HO‐1 inhibition downregulate IDO1 and ARG‐2 gene expression, but also reduced IDO1 enzymatic activity. Moreover, T cell activation status affected PD‐L1 expression and IDO1 activity, which were upregulated in the presence of activated, but not resting, T cells. Our results highlight the crucial role of HO‐1 in the immunosuppressive activity of macrophages in the GBM TME and demonstrate the feasibility of reprogramming them as an alternative therapeutic strategy for restoring immune surveillance. Abstract : What's new? Macrophages are vital for normal iron homeostasis and contribute to dysregulated iron metabolism in the tumor microenvironment. In glioblastoma, macrophages also play a role in immunosuppression. This study shows that the immunosuppressive activity of bone marrow‐derived macrophages (BMDMs) in glioblastoma is linked to iron metabolism. Inhibition of heme oxygenase‐1 (HO‐1), the central enzyme of the heme catabolism pathway, abolished the immunosuppressive activity of BMDMs. This effect simultaneously modulated other downstream inhibitory mechanisms, including IL‐10 and IDO1 and ARG2, which are involved in l ‐arginine and l ‐tryptophan catabolism. Targeting HO‐1 is a promising strategy for restoring immune surveillance in the tumor microenvironment.